The implementation of grading systems for beef carcass value differentiation: the Uruguayan experience. - BRITO, G. (2024)
Implications: * The Uruguayan beef industry is moving from a subjective beef carcass grading system to a video image analysis (VIA). Different studies contributed to this. Three Uruguayan Beef Quality Audits showed that 80% of the carcasses received the same muscle conformation and fatness score. This lack of discrimination associated suggested the need to develop a more discriminatory method of sorting carcasses into uniform marketing groups. The beef marketing system in Uruguay is based on hot carcass weight and visual degree of fat cover, creating a price grid in which the heaviest carcasses with fat grade 2 are rewarded, achieving the requirements of markets. * Research has been conducted in Uruguay using ultrasound of live animal and VIA of hot and chilled carcasses to better predict red meat yield. The results from this research will be discussed.* As the meat industry moves toward these concepts, a payment system that remunerates the individual animal merit is necessary, allowing the producer to undertake the relevant changes. Copyright © 2024 American Society of Animal Science